MAP4K4 associates with BIK1 to regulate plant innate immunity. (2nd September 2019) - Jiang, Yunhe; Han, Baoda; Zhang, Huoming; Mariappan, Kiruthiga G; Bigeard, Jean; Colcombet, Jean; Hirt, Heribert
Abstract: To perceive pathogens, plants employ pattern recognition receptor (PRR) complexes, which then transmit these signals via the receptor‐like cytoplasmic kinase BIK1 to induce defense responses. How BIK1 activity and stability are controlled is still not completely understood. Here, we show that the Hippo/STE20 homolog MAP4K4 regulates BIK1‐mediated immune responses. MAP4K4 associates and phosphorylates BIK1 at Ser233, Ser236, and Thr242 to ensure BIK1 stability and activity. Furthermore, MAP4K4 phosphorylates PP2C38 at Ser77 to enable flg22‐induced BIK1 activation. Our results uncover that a Hippo/STE20 homolog, MAP4K4, maintains the homeostasis of the central immune component BIK1. Synopsis: The receptor‐like cytoplasmic kinase BIK1 serves as a central signaling hub during PAMP‐triggered immunity in plants. The kinase MAP4K4 targets and phosphorylates BIK1, thereby stabilizing the protein, and promoting BIK1 activation. MAP4K4 is required for flg22‐triggered immune responses. MAP4K4 binds and phosphorylates BIK1 at Ser233, Ser236 and Thr242 to promote its stability and activity. MAP4K4 phosphorylates PP2C38 at Ser77 to promote flg22‐induced BIK1 activation. Abstract : The receptor‐like cytoplasmic kinase BIK1 serves as a central signaling hub during PAMP‐triggered immunity in plants. The kinase MAP4K4 targets and phosphorylates BIK1, thereby stabilizing the protein, and promoting BIK1 activation.